Penggunaan Bahasa Indonesia oleh Mahasiswa Program Studi Pariwisata Stiepar Yapari - Avrilia Rosdina Ristandi; Lutfiah Damayanti (Tamasya : Jurnal Pariwisata Indonesia, 2025)
This study aims to analyze the use of Indonesian by students of the Tourism Study Program at STIEPAR Yapari in an academic context. Indonesian as a national language plays an important role in effective communication in higher education environments. The research method used is a qualitative descriptive approach, with data collection techniques through observation, interviews, and document analysis. The results of the study indicate that students still tend to use informal language and mix foreign terms in academic communication, which results in grammatical errors and hinders understanding of the material. Several factors that influence this language use pattern include daily habits, the influence of social media, and the dominance of foreign languages. This study is expected to contribute to improving the quality of Indonesian language use among students, as well as providing recommendations for lecturers and institutions in more effective language learning.